The importance of physical activity in the regulation of anti-viral immunity - R. A. Khanferyan; I. V. Radysh; V. V. Surovtsev; M. M. Korosteleva; I. V. Aleshina (National Electronic Information Consortium (NEICON), 2020)
The paper reviews the current data on the effect and role of varying intensity physical activity in the prevention of various respiratory virus infections, including influenza virus and SARS-CoV-2 coronavirus. The paper discusses the effect of varying intensity physical activity on antiviral immunity, cellular and cytokine responses to respiratory virus infections, physical activity influence on vaccination effectiveness and the role of regular moderate intensity physical activity in the prevention of viral infection in patients with obesity, overweight, diabetes and other metabolic disorders. The paper analyzes physical activity role in the prevention of SARS-CoV-2 infection, as well as in the conditions of self-isolation and quarantine.